Procedures Related Pain Management in Newborns: A Narrative Review - Samira Jaouhar; Zainab Toujami; Rachid Flouchi; Dounia Benammi; Omaima El Bouazzi (Journal of the Dow University of Health Sciences)
Pain is one of the most common issues in sick newborns, particularly those requiring intensive care. Relieving pain and helping newborns develop coping mechanisms are the primary objectives of pain management. Pain management in neonates presents multifaceted challenges due to their inability to self-report discomfort. A comprehensive literature review was conducted using databases such as PubMed, Scopus, Web of Science, and Google Scholar, including studies published between 1990 and 2022 based on predefined criteria. This review explores various aspects of pain assessment and management in newborns. Non-pharmacological interventions, such as skin-to-skin care, oral sucrose, music therapy, swaddling, therapeutic touch, and breastfeeding, are highly effective, with oral sucrose shown to reduce procedural pain scores in some studies. Pharmacological approaches, including opioid-free analgesics, opioids, and local anesthetics, are effective in managing neonatal pain. However, their use requires careful monitoring due to the potential for adverse effects, particularly with opioids. Nurses and parents play pivotal roles in neonatal pain management. Nurses, skilled in assessment tools and interventions, monitor and administer medications while employing non-pharmacological methods. Educating and involving parents significantly contribute to alleviating neonatal pain, with parental presence and active participation during procedures shown to reduce stress and improve outcomes.